STUDI DESKRIPTIF TERHADAP PENURUNAN EFIKASI GURU SELAMA PEMBERLAKUAN PEMBELAJARAN ONLINE - Charli Sitinjak; Gibson Manalu; Hafizh Zain Abdillah (Program Studi S1 Psikologi, 2021)
Coronavirus disease (2019) or what we usually call COVID-19 has had a significant impact on all sectors, including the education sector. The transition from traditional or face-to-face teaching to an online teaching system. Has given a lot of homework for teachers, they have to work hard to be able to adapt quickly to the changes. In addition, this online learning process places a heavy burden on teachers. This makes teachers stressed and affects teacher performance. This study aims to describe the problems faced by teachers seen from the teacher's self-efficacy during teaching using the online method. 40 teachers participated in this study, where they were asked to fill out a teacher self-efficacy scale (TSE) to measure their self-efficacy. The results showed that there was a significant decrease in the self-efficacy of senior teachers when teaching using the online method